EFEK PERLOKUSI TINDAK TUTUR DIREKTIF DALAM HIPNOTERAPI: ANALISIS NEUROPRAGMATIK - Jatmika Nurhadi, - (2023)
Hypnotherapy is a therapy that uses the state of hypnosis (trance), which is a state of consciousness when a person is relaxed and focused so that it is easier to receive advice. Hypnotherapy is a type of therapy that uses linguistic features in a speech to change a person's level of consciousness by involving internal and imaginative processes to help a person receive suggestions. Hypnotherapists use various types of speech acts, especially directive speech acts. This research intends to reveal the perlocutionary effect of directive speech acts in hypnotherapy, which is the consequential influence of using speech acts. In this research, I used neuro pragmatics to analyze the perlocutionary effect. This analysis is used to answer three main problems in this study, namely: (1) the function and type of directive perlocutionary acts; (2) the perlocutionary effect of directive speech acts on changes in mental state based on differences in frequency range, and (3) the perlocutionary effect of directive speech acts on brain image. The method used in this research is a mixed method with multiple case studies. Data collection was conducted in two steps, qualitative data were collected from the transcription of five hypnotherapy inductions (Indonesian Board of Hypnotherapy), while quantitative data were collected by electroencephalography (EEG) recording. Thirty-eight participants were native Indonesian speakers, right-handed, and had no history of diagnosed neurocognitive disease. Then the qualitative data were analyzed for function using the Enaction Model (Ballmer & Brennenstuhl, 1981), while the type was analyzed using the Directness Scale (Blum-Kulka et al., 1989; Blum-Kulka & Olshtain, 1984). Meanwhile, the quantitative analysis used Paired Sample T Test and Cohen's D Test to test the mean difference of Prestimulus and Speech Act Verb (SAV), and while the brain image was studied by standardized Low-Resolution Electromagnetic Brain Tomography (sLORETA) analysis (Pascual-Marqui, 2001, 2002; Pascual-Marqui et al., 1994). The results of this study, perlocutionary acts, are divided into eight functions, different SAV, namely Desiring, Focusing, Requesting, Pleading, Commanding, Calming, Restraining, and Preventing. Then based on the type, there are Mood Derivable, Performatives, Want Statements, and Strong Hints. Then, based on the Paired Sample T Test, most of the SAVs significantly (p < 0.01) increased activity in Alpha and Theta waves but decreased Beta and Delta wave activity very particularly (p > 0.001). Then the results of brain images based on sLORETA were found to have a dominant effect on most of the left hemisphere (41 utterances) and a small part of the right hemisphere (22 utterances). Then a strong effect on the parietal lobe, followed by the occipital lobe. Then the results are based on the lobe, and the parietal lobe is the lobe that has the most electrical activity in the brain. Then based on the division of the Brodmann Area (Brodmann, 2006), 13 areas were affected, while Brodmann 7 is the area with the most electrical activity. This result implies that hypnotherapy speech acts have a strong pragmatic power toward what happens in the brain.